2021
DOI: 10.3390/ma14216234
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Mechanical Properties and Durability of High-Content Hybrid Fiber–Polymer Concrete

Abstract: Polymer-modified concrete and fiber concrete are two excellent paving materials that improve the performance of some concrete, but the performance of single application material is still limited. In this paper, polymer-modified concrete with strong deformation and fiber concrete with obvious crack resistance and reinforcement effect were compounded by using the idea of composite material design so as to obtain a high-performance pavement material. The basic mechanical properties of high-content hybrid fiber–po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…[10] steel, basalt polypropylene 1.5 1.25 [14] steel ultrashort ultrafine steel polypropylene 1.92 4.0 0.27 [17] steel 2 [18] Kevlar + carbon 1.0 [19] nylon + jute 1.0 [20] steel, polypropylene 0.25-0.45 [21] PVA steel 1.0-2.0 1.5-4.0 [30] glass, basalt 0.25-2.0 [31] glass 0.5-3.0 [32] glass, polypropylene 0.5-2.0…”
Section: Research Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…[10] steel, basalt polypropylene 1.5 1.25 [14] steel ultrashort ultrafine steel polypropylene 1.92 4.0 0.27 [17] steel 2 [18] Kevlar + carbon 1.0 [19] nylon + jute 1.0 [20] steel, polypropylene 0.25-0.45 [21] PVA steel 1.0-2.0 1.5-4.0 [30] glass, basalt 0.25-2.0 [31] glass 0.5-3.0 [32] glass, polypropylene 0.5-2.0…”
Section: Research Sourcesmentioning
confidence: 99%
“…Arbitrary orientation is carried out, as a rule, with short fibers, but in this case, roll materials in the form of canvases, mats, and veils, in which the fibers do not have an organized weave, can also be used. In practice, various types of arbitrary orientation can be implemented in structures [10][11][12][13][14][15]. Plane-arbitrary orientation is characterized by an equiprobable and unlimited (free and chaotic) distribution of fibers in a plane (in two-dimensional space).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, none of the existing studies has reported high fibre admixtures for polymeric concrete, with a typical fibre admixture of no more than 3% by volume 34, 41. To further improve cracking resistance and achieve ultra-high toughness, a series of high-performance polymer concretes with high strength, toughness, and environmental adaptability has been studied and realised 35 37 by the authors. As reported in the literature 37 , hybrid fibre polymer concrete exhibits reliable working performance, with the elastic modulus, compressive strength, and flexural strength reaching up to 35.93 GPa, 52.82 MPa, and 11.51 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%